Risk of miscarriage following amniocentesis or chorionic villus sampling: systematic review of literature and updated meta‐analysis. (6th September 2019) - Salomon, L. J.; Sotiriadis, A.; Wulff, C. B.; Odibo, A.; Akolekar, R.
ABSTRACT: Objective: To estimate the procedure‐related risk of miscarriage after amniocentesis and chorionic villus sampling (CVS) based on a systematic review of the literature and an updated meta‐analysis. Methods: A search of MEDLINE, EMBASE and The Cochrane Library was carried out to identify studies reporting complications following CVS or amniocentesis. Eligible for inclusion were large controlled studies reporting data for pregnancy loss prior to 24 weeks' gestation. Study authors were contacted when required to identify additional necessary data. Data for cases that had an invasive procedure and controls were inputted into contingency tables and the risk of miscarriage was estimated for each study. Summary statistics based on a random‐effects model were calculated after taking into account the weighting for each study included in the systematic review. Procedure‐related risk of miscarriage was estimated as a weighted risk difference from the summary statistics for cases and controls. Subgroup analyses were performed according to the similarity in risk levels for chromosomal abnormality between the invasive‐testing and control groups. Heterogeneity was assessed using the I 2 statistic. Egger's bias was estimated to assess reporting bias in published studies. Results: The electronic search yielded 2943 potential citations, from which 12 controlled studies for amniocentesis and seven for CVS were selected for inclusion in the systematic review. A total of 580 miscarriages occurred following 63 723 amniocentesis procedures, resulting in a weighted risk of pregnancy loss of 0.91% (95% CI, 0.73–1.09%). In the control group, there were 1726 miscarriages in 330 469 pregnancies with a loss rate of 0.58% (95% CI, 0.47–0.70%). The weighted procedure‐related risk of miscarriage following amniocentesis was 0.30% (95% CI, 0.11–0.49%; I 2 = 70.1%). A total of 163 miscarriages occurred following 13 011 CVS procedures, resulting in a risk of pregnancy loss of 1.39% (95% CI, 0.76–2.02%). In the control group, there were 1946 miscarriages in 232 680 pregnancies with a loss rate of 1.23% (95% CI, 0.86–1.59%). The weighted procedure‐related risk of miscarriage following CVS was 0.20% (95% CI, −0.13 to 0.52%; I 2 = 52.7%). However, when studies including only women with similar risk profiles for chromosomal abnormality in the intervention and control groups were considered, the procedure‐related risk for amniocentesis was 0.12% (95% CI, −0.05 to 0.30%; I 2 = 44.1%) and for CVS it was −0.11% (95% CI, −0.29 to 0.08%; I 2 = 0%). Conclusions: The procedure‐related risks of miscarriage following amniocentesis and CVS are lower than currently quoted to women. The risk appears to be negligible when these interventions were compared to control groups of the same risk profile. Copyright © 2019 ISUOG. Published by John Wiley & Sons Ltd. Abstract : A video abstract of this article is availablehere This article's abstract has been translated into Spanish and Chinese. Follow the links from theabstract to view the translations. This article has been selected for Journal Club. Clickhere to view slides and discussion points. RESUMEN: Riesgo de aborto después de una amniocentesis o una biopsia de vellosidades coriónicas: revisión sistemática de bibliografía y metaanálisis actualizado Objetivo: Estimar el riesgo de aborto relacionado con el procedimiento de la amniocentesis o la biopsia de vellosidades coriónicas (BVC) mediante una revisión sistemática de bibliografía y un metaanálisis actualizado. Métodos: Se realizó una búsqueda en MEDLINE, EMBASE y The Cochrane Library para identificar estudios que reportaron sobre complicaciones después de una BVC o amniocentesis. Se consideraron elegibles para su inclusión los estudios controlados de gran tamaño que reportaron datos sobre la pérdida del embarazo antes de las 24 semanas de gestación. Se estableció contacto con los autores de los estudios cuando fue necesario para identificar datos adicionales necesarios. Se introdujeron en tablas de contingencia los datos de los casos que se sometieron a un procedimiento invasivo y controles y se estimó el riesgo de aborto para cada estudio. Las estadísticas resumen basadas en un modelo de efectos aleatorios se calcularon después de tener en cuenta la ponderación para cada estudio incluido en la revisión sistemática. El riesgo de aborto relacionado con cada procedimiento se estimó como una diferencia de riesgo ponderada de las estadísticas resumen para los casos y controles. Los análisis de subgrupos se realizaron de acuerdo con la similitud en los niveles de riesgo de anomalías cromosómicas entre los grupos de prueba invasiva y de control. La heterogeneidad se evaluó mediante el test estadístico I 2 . Se estimó el sesgo de Egger para evaluar el sesgo de información reportada en los estudios publicados. Resultados: La búsqueda electrónica arrojó 2943 citas potenciales, de las cuales se seleccionaron para su inclusión en la revisión sistemática 12 estudios controlados para la amniocentesis y siete para la BVC. Después de los 63723 procedimientos de amniocentesis sucedieron un total de 580 abortos, lo que resultó en un riesgo ponderado de pérdida de embarazo del 0, 91% (IC 95%, 0, 73–1, 09%). En el grupo de control hubo 1726 abortos en 330469 embarazos, con una tasa de pérdida del 0, 58% (IC 95%, 0, 47–0, 70%). El riesgo ponderado de aborto relacionado con el procedimiento de amniocentesis fue del 0, 30% (IC 95%, 0, 11–0, 49%; I 2 = 70, 1%). Después de 13011 procedimientos de BVC se produjeron un total de 163 abortos, lo que resultó en un riesgo de pérdida de embarazo del 1, 39% (IC 95%, 0, 76–2, 02%). En el grupo de control hubo 1946 abortos en 232680 embarazos, lo que supuso una tasa de pérdida del 1, 23% (IC 95%, 0, 86–1, 59%). El riesgo ponderado de aborto relacionado con el procedimiento de BVC fue de 0, 20% (IC 95%, ‐0, 13–0, 52%; I 2 = 52, 7%). Sin embargo, cuando se consideraron los estudios que incluyeron sólo mujeres con perfiles de riesgo similares para la anomalía cromosómica en los grupos de intervención y control, el riesgo relacionado con el procedimiento de la amniocentesis fue de 0, 12% (IC 95%, ‐0, 05–0, 30%; I 2 = 44.1%) y para el MVC fue de ‐0, 11% (IC 95%, ‐0, 29–0, 08%; I 2 = 0%). Conclusiones: Los riesgos de aborto relacionados con el procedimiento de la amniocentesis y la BVC son menores que los actualmente mencionados a las mujeres. El riesgo parece ser insignificante cuando estas intervenciones se compararon con grupos de control del mismo perfil de riesgo. 摘要: 羊膜穿刺术或绒毛膜绒毛取样后的流产风险:相关文献的系统评估及最新的元分析 目标: 依据相关文献的系统评估及最新的元分析，估算羊膜穿刺术与绒毛膜绒毛取样(CVS)后的程序相关性流产风险。 方法: 检索了MEDLINE、EMBASE及科克伦图书馆藏文献(Cochrane Library)，寻找一些报告CVS或羊膜穿刺术之后出现并发症的研究案例。符合纳入标准的是妊娠24周前报告妊娠失败数据的大型对照研究。需要时联系了研究作者，以确定其他必要的数据。将几个侵入性程序与对照案例的数据输入了列联表，估算了每项研究的流产风险。考虑了系统评估中包括的每项研究的权重后，计算了基于随机效应模型的汇总统计。针对相关案例和对照组汇总统计数据，以加权风险差异的形式估算了程序相关性流产风险。根据侵入性测试组和对照组之间的染色体异常风险水平相似性，进行了亚组分析。通过 I 2 统计进行了异质性评估。估算了艾格偏差，以评估已发表的研究报告中的报告偏差。 结果: 在线检索发现了2943例潜在的引述案例，从中选出12例羊膜穿刺术对照研究案例和7例CVS案例，纳入系统评估范畴。63 723例羊膜穿刺术之后，总共有580例流产案例，相应的妊娠失败加权风险为0.91% (95% CI, 0.73‐1.09%)。在对照组中，330 469例妊娠中有1726例流产案例，妊娠失败率为0.58% (95% CI, 0.47‐0.70%)。羊膜穿刺术之后的程序相关性加权流产风险为0.30% (95% CI, 0.11‐0.49%; I 2 =70.1%)。13 011 CVS程序之后总共发生了163例流产，相应的妊娠失败风险为1.39% (95% CI, 0.76‐2.02%)。在对照组中，232 680例妊娠中有1946例流产案例，妊娠失败率为1.23% (95% CI, 0.86‐1.59%)。CVS之后的程序相关性加权流产风险为0.20% (95% CI, 0.13‐0.52%; I 2 =52.7%)。但在考虑一些只在干预组和对照组中纳入相似染色体异常风险特征的女性受试者的研究项目时，羊膜穿刺术的程序相关性风险为0.12% (95% CI, 0.05‐0.30%; I 2 =44.1%)，CVS则为0.11% (95% CI, 0.29‐0.08%; I 2 =0%)。 结论: 羊膜穿刺术和CVS之后的程序相关性流产风险低于当前引述的水平。将这些干预组和具有相同风险特征的对照组进行比较后发现，风险似乎可以忽略不计。